Reducing morbidity in radial forearm free flap donor site: a review of closure techniques. Issue 5 (24th October 2022) - Patel, Rusha
Abstract : Purpose: Radial forearm free tissue transfer (RFFF) has been an extremely reliable reconstructive option for head and neck oncologic defects for over 30 years. With high reliability, interest has shifted in minimizing donor site morbidity, much of which results from closure techniques. Recent findings: Portable negative pressure wound devices, newer dermal substitutes, and local flap techniques have improved donor site aesthetics and function. Summary: Outcomes of the RFFF donor site may benefit from newer techniques in closure.